Nilai Etika dalam Seni Islam: Studi Pemikiran Seyyed Hossein Nasr - Farkhan Fuady (Jurnal Peradaban, 2022)
The development of thought and creativity in Islamic art is increasingly showing progress. Artworks provide teachings in everyday life that are useful for creating good Muslims. Various Muslim scholars also studied Islamic art and even Muslims produced Islamic art. One of them is Seyyed Hossein Nasr who approaches Islamic art with spirituality. This research is a library research or literature with qualitative research methods. Research library data sources from books, manuscripts, scientific articles and other sources of literature that can be trusted. One of the primary data sources is Seyyed Hossein Nasr's book entitled Islamic Art and Spirituality which has been translated into Indonesian by Sutejo with the title Spirituality and Islamic Art. The results show that Islamic art contains ethical values ​​that are useful for everyday life. As in the art of calligraphy which is attached to the lives of Muslims, such as in household furniture. In addition, Islamic teachings can be seen in Islamic poems. Other arts also such as music, dance, Islamic architecture and others. So it can be concluded that Islamic art contains ethical values ​​which for Nasr can be contemplated through spiritual activities.